Depressive symptoms are associated with fasting insulin resistance in obese youth. Issue 5 (26th May 2014) - Hannon, T. S.; Li, Z.; Tu, W.; Huber, J. N.; Carroll, A. E.; Lagges, A. M.; Gupta, S.
Summary Background In adults, depressive symptoms are positively associated with insulin resistance. Objective To determine whether an association exists between depressive symptoms and markers of insulin resistance in youth. Methods This study used a retrospective review of data from an obesity clinic. We evaluated the association between depressive symptoms (Children's Depression Inventory, CDI) and fasting insulin and homeostatic model assessment‐insulin resistance (HOMA‐IR) in obese youth (n = 207, age 10–18 years). Individuals with lower vs. higher CDI T‐scores (<65 vs. ≥65) were compared; this cut‐point is accepted as indicating the possibility of clinical depression. Multiple linear regression was used to evaluate relationships between CDI T‐scores and insulin resistance. Results Fasting insulin and HOMA‐IR values were 40% higher in patients with higher CDI T‐scores (P = 0.04). After accounting for gender, race, age and body mass index, CDI T‐score remained associated with HOMA‐IR, although the strength of the association was small (b = 0.007, P = 0.049). Conclusions Relationships between depressive symptoms and insulin resistance should be considered when evaluating obese youth.